Balancing Agricultural Production and Environmental Protection in the Tri-County Agricultural Area: Results from Stakeholder Discussions - Tatiana Borisova; Laila Racevskis; Bryan Fluech; Jane Provancha (EDIS)
FE826, a 6-page illustrated fact sheet by Tatiana Borisova, Laila Racevskis, Bryan Fluech, and Jane Provancha, summarizes key points from discussions with various stakeholders in the Putnam, St. Johns, and Flagler tri-county agricultural area during a session of the Florida Natural Resources Leadership Institute held in May of 2008. The discussions focused on the issues of balancing agricultural production and environmental protection in the region. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.